2003
DOI: 10.1093/ejil/14.1.141
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting State Succession to Humanitarian Treaties: Is There a Case for Automaticity?

Abstract: When the law is able to distinguish clearly between the different categories of treaties in terms of purpose and function, it will have taken an important step forward. .. When that stage is reached, those treaties which are immediately available to a new State will, it is safe to predict, be so because of their purpose and function and not because of a 'succession' from the parent State; it is precisely because law at present makes provision only for succession that the decision to become party or not is prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 4 publications
0
4
0
2
Order By: Relevance
“…[50] With respect to human rights treaties, the question of 'automatic succession' and its customary nature is even more pronounced, with views ranging from acceptance to outright rejection (Jenks [1952] at 142;Müllerson [1994] at 154-7; Bos [1995] at 18; Kamminga [1996] at 472-3;Shaw [1994] at 84; Stern [1996] at 297-306; Higgins [1998] at 696-7;Rasulov [2003]; Ruiz [2011] at 69; Zimmermann and Devaney [2019]).…”
Section: Succession To Human Rights Treatiesmentioning
confidence: 99%
“…[50] With respect to human rights treaties, the question of 'automatic succession' and its customary nature is even more pronounced, with views ranging from acceptance to outright rejection (Jenks [1952] at 142;Müllerson [1994] at 154-7; Bos [1995] at 18; Kamminga [1996] at 472-3;Shaw [1994] at 84; Stern [1996] at 297-306; Higgins [1998] at 696-7;Rasulov [2003]; Ruiz [2011] at 69; Zimmermann and Devaney [2019]).…”
Section: Succession To Human Rights Treatiesmentioning
confidence: 99%
“…Dakle, u svakom konkretnom slučaju potrebno je utvrđivati mogućnost i uslove primene običajne norme na međunarodne organizacije. 65 Upravo iz ovog razloga neki autori smatraju da je primena, na primer, obaveza poštovanja ljudskih prava na međunarodne organizacije problematična. 66 Tako Alvarez, u kontekstu primene nekih odredaba ugovora o ljudskim pravima na UN kaže kako je teško mnoge od tih obaveza staviti u kontekst polja delovanja ove organizacije.…”
Section: Pravila Međunarodnog Prava Koja Imaju Status Običaja I Njihounclassified
“…Kako Alvarez i sam primećuje, to su situacije u kojima UN vrši mirovne operacije i/ili sprovodi administrativnu upravu neke teritorije (kao što je slučaj s UN u Kambodži 1992, Kosovu i Istočnom Timoru 1999). 69 Upravo se u tim situacijama pitanje 65…”
Section: Pravila Međunarodnog Prava Koja Imaju Status Običaja I Njihounclassified
“…the system of law applied to these agreements cannot be public international law stricto sensu, because these agreements are not inter-state agreements and do not deal with inter-state relations. He suggested that the legal system of law most likely suitable for the regulation of these agreements and the adjudication of disputes arising out of them is the general principles of law recognised by civilised nations (McNair, 1961; Quoted by Rasulov, 2003).…”
Section: Dualism Preferred Over Monism International Contract Principlesmentioning
confidence: 99%
“…3.3.1 The application of the general principles of law. The idea that economic development agreements can be governed by general principles of law was presented by McNair (1961) Quoted that Rasulov, 2003). He argued that:…”
Section: Dualism Preferred Over Monism International Contract Principlesmentioning
confidence: 99%